2017
DOI: 10.1177/2045125317743435
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulation for the treatment of eating disorders and obesity

Abstract: Eating disorders and obesity adversely affect individuals both medically and psychologically, leading to reduced life expectancy and poor quality of life. While there exist a number of treatments for anorexia, morbid obesity and bulimia, many patients do not respond favorably to current behavioral, medical or bariatric surgical management. Neuromodulation has been postulated as a potential treatment for eating disorders and obesity. In particular, deep brain stimulation and transcranial non-invasive brain stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 179 publications
(209 reference statements)
1
37
0
3
Order By: Relevance
“…40,61 Other theoretical targets include the medial and lateral orbitofrontal cortex, medial prefrontal cortex, ventral pallidum, caudate, insula, anterior cingulate cortex (ACC), amygdala, putamen, and hippocampus. 55 Similar to other DBS indications, early evidence for DBS treatment originated from the benefits of lesioning procedures, such as leukotomy, 65,69 thalamotomy, 91 and capsulotomy for anorexia nervosa. 6 Moreover, there is evidence for network dysfunction associated with selfawareness (insula, parietal cortex); visual and gustatory sensation (occipital cortex, insula); and the reward pathway (ventral striatum, ACC, subgenual cingulate cortex).…”
Section: Eating Disorders and Obesitymentioning
confidence: 99%
“…40,61 Other theoretical targets include the medial and lateral orbitofrontal cortex, medial prefrontal cortex, ventral pallidum, caudate, insula, anterior cingulate cortex (ACC), amygdala, putamen, and hippocampus. 55 Similar to other DBS indications, early evidence for DBS treatment originated from the benefits of lesioning procedures, such as leukotomy, 65,69 thalamotomy, 91 and capsulotomy for anorexia nervosa. 6 Moreover, there is evidence for network dysfunction associated with selfawareness (insula, parietal cortex); visual and gustatory sensation (occipital cortex, insula); and the reward pathway (ventral striatum, ACC, subgenual cingulate cortex).…”
Section: Eating Disorders and Obesitymentioning
confidence: 99%
“…In 1974, Quaade et al reported on three patients undergoing stereotactic RF ablation of the lateral hypothalamus in an area where electrical stimulation was able to evoke hunger-related responses, which were not further specified. These patients showed a statistically significant, but transient, decrease from preoperative to postoperative spontaneous calorie intake, while body weight decreased slightly and temporarily, not being significantly affected [91,97].…”
Section: Eating Disordersmentioning
confidence: 80%
“…To date, six studies have examined the role of ablative procedures in patients with severe AN [91]. The targets for ablation were the frontal lobe white matter [86,92], the dorsomedial thalamus [93] and more recently the ALIC [94,95] and Nac [96].…”
Section: Eating Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Advancements in preclinical and neuroimaging research studies and neurosurgical experiences led to a discovery of several targets that could prove beneficial to numerous diseases. DBS in the ventral capsule, the ventral striatum, or nucleus accumbens (NA) has been shown to improve symptoms of obsessive-compulsive disorder [13], while NA stimulation has been shown to reduce the severity of obesity and anorexia [14]. Treating treatment-resistant depression is also possible with DBS; however it requires an individualized approach due to numerous possible targets [15].…”
Section: Introductionmentioning
confidence: 99%